Effects of moisture on the puffing ratio of rice and storage study of puffed rice - Pamparo, Melissa Rayala; Tavora-Mateo, Liwayway (1992.)
This study determined the effect of moisture on the puffing ratio of rice and the storage stability of sugar coated puffed rice. Statistical analysis of the results obtained showed that there was no significant difference on the moisture content of the three raw milled rice varieties, however, expansion ratio of a particular variety was found to be greatly influenced by its moisture content before production. The second phase of the study was divided into two subphases. The sorption isotherms, determined in the first subphase, exhibited sigmoidal-shaped curves for the three varieties of puffed rice. The three SI curves differed in height which is attributed to their varying degrees of hygroscopicity. The second subphase of the study involved the packaging of the product using three different packaging materials-polyethylene, high density polyethylene and polypropylene. Product shelf-life was estimated and the changes in quality attributes during storage were monitored. Rate of deterioration was fast in high density polyethylene for all samples but slow in polypropylene. Among the three packaging materials, polypropylene was the most suitable packaging material as IR-76 was evaluated as the best rice variety suited in puffed rice manufacture having good quality attributes. Product shelf-life using IR-76 rice variety as raw material and polypropylene as packaging material was estimated to be 14 days at ambient condition. Moisture content is a critical parameter in the production and storage of puffed rice since it is a determinant of the general acceptability of the product. As moisture content increases, product attributes deteriorate, hence, general acceptability of the product decreases.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Rice